2016
DOI: 10.1007/s11130-016-0561-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fruit Pomace Addition on Shortbread Cookies to Improve Their Physical and Nutritional Values

Abstract: Fruit pomace remaining after juice extraction is still a source of bioactive compounds. Especially rich in these compounds is the pomace from blackcurrant fruit and from fruits of little-known horticultural plants, like: rowan, rosehip and elderberry. The addition of fruit pomace to bakery and confectionery products, especially to those made of white flour, may significantly enrich their composition with dietary fiber, vitamins and phenolic compounds. This study was aimed at determining the effect of 20 % addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 19 publications
0
54
0
5
Order By: Relevance
“…Ciccoritti, Paliotta, Centioni, Mencarelli, and Carbone () obtained values from 6.6 to 582 mg/100 g for pomace in two varieties of cherries subjected to different heat treatments. For blackcurrant pomace, in turn, the respective values vary from 8.34 to 113 mg/100 g (Pieszka et al, ; Tańska et al, ). During extrusion process the antioxidants level was decreased by 25% for sour cherry extrudate and five times for black currant extrudates.…”
Section: Resultsmentioning
confidence: 99%
“…Ciccoritti, Paliotta, Centioni, Mencarelli, and Carbone () obtained values from 6.6 to 582 mg/100 g for pomace in two varieties of cherries subjected to different heat treatments. For blackcurrant pomace, in turn, the respective values vary from 8.34 to 113 mg/100 g (Pieszka et al, ; Tańska et al, ). During extrusion process the antioxidants level was decreased by 25% for sour cherry extrudate and five times for black currant extrudates.…”
Section: Resultsmentioning
confidence: 99%
“…Producing berry-based juice generates by-products, comprising peel and seeds, having a high nutritional value because of their polyphenol and fiber content. Berry by-products can be a value-added food ingredient [2][3][4] and recent studies show that the enrichment of food products with these by-products is feasible [5][6][7]. In this context, chokeberry (Aronia melanocarpa) pomace can be used, as chokeberry is one of the richest plant sources of phenolic phytochemicals, including procyanidins and anthocyanins [8,9] which are related to effectiveness in several pathological conditions where damage is caused by uncontrolled oxidative processes [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, concerns about lower sensory quality may arise. The study of Tańska et al (2016) showed that cookies with the addition of fruit pomaces exhibited acceptable sensory properties parallel to increased content of dietary fibre and higher antioxidant potential. Nevertheless, the amount of the additive incorporated might be a limiting factor (Ajila et al, 2008;Mildner-Szkudlarz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%